Study of the immunogenicity of the cell death induced by the activation of CD47 in tumor cells - Calvillo Rodríguez, Kenny Misael (2019)
CD47 activation by peptides derived from the C-terminal domain of thrombospondin-1, such as PKHB1, induces regulated cell death (RCD) in different types of cancer cells. The RCD induced by the activation of CD47 is characterized by being independent of caspases, calcium dependent, generating morphological changes in the endoplasmic reticulum (ER) and the exposure of calreticulin (CRT) in chronic lymphocytic leukemia (CLL) cells. On the other hand, ER stress and CRT exposure are characteristics of immunogenic cell death (ICD). Based on the above, the objective of this thesis was to determine the immunogenicity of cell death induced by the activation of CD47 in lymphoma and breast cancer cells. To this end, ICD’s characteristics were evaluated, such as damage associated molecular patterns (DAMPs) exposure or release and their effect on the activation of an antitumor immune response. In addition, the extent of the immunogenicity of death was evaluated by prophylactic and therapeutic vaccinations, with lysates of cancer cells treated with PKHB1 (PKHB1-TCL) on the tumor establishment of lymphoma and breast cancer (in vivo), as well as their capacity to generate a long-term anti-tumor immunological memory. The results obtained allow us to demonstrate that PKHB1 induces CRT exposure and release of CRT and HSP90 in lymphoma and breast cancer cells. It was also demonstrated that the PKHB1-TCL promotes the maturation of dendritic cells (DCs) increasing the expression of maturation markers CD80, CD86 and the release of TNFa. Furthermore, the PKHB1-TCL activated the antitumor immune response (ex vivo), promoting the specific cytotoxicity of tumor cells by T lymphocytes and induced the inflammatory cytokines IL-2 and IFNg release. Finally, it was demonstrated that the PKHB1-TCL is able to prevent the tumor establishment in a lymphoma and murine breast cancer model, and to induce a long-term immunological anti-tumor memory. Finally, when observing that the immunogenic characteristics of death are shared among the different tumor models, we can propose that the CD47 activation by PKHB1 induces a conserved ICD mechanism, enhancing its application and making it a promising antitumor therapy.